" The role of Iraqi women in political participation after 2005 " - Reem Dhaif Abdulmajeed (Tikrit Journal For Political Science, 2023)
The overall objective of the research is to know the concept and importance of political participation and, in particular, to identify women's political participation and the importance of participation and political interests of Iraqi women, and assumed that Iraqi women had a constructive power not only in political positions but also in all areas of economic, educational, professional and other life It also addresses women's rights, whether political, economic or social. The impulse of women in Iraq is a driving environment if it is a social and cultural environment with its various components of customs and traditions to reach advanced degrees in various social, economic, cultural, educational and political activities. s political rights through increased educational opportunities for women and their ability to enter employment and to assume important positions. Iraqi women have attained a high educational and cultural level and the rights between men and women are equal in all rights. However, at the political level, women fall far short of their rights. They have several positions in government. Women's ministerial or government representation on ministries is less important than men's in government. After 2005, however, this was demonstrated by Iraqi women's leadership of important positions in the State economically, socially, educationally and culturally. The political awareness of Iraqi women lies in the importance of exercising their political rights through increased educational opportunities for women and their ability to enter employment and to hold important positions.